The Process of internalizing Multicultural Values in Religious Educational Institutions Islamic Booarding Schools - siyono; Adi Wiyanto (MultiTech Publisher, 2023)
Article with the title Internalization of Multicultural Values in Islamic boarding school religious institutions in Semarang Regency, Central Java, Indonesia. The formulation of the problem in this study article uses a type of descriptive research with a qualitative approach, the location of this research was carried out at a religious institution Islamic boarding school in Semarang regency. Data sources were obtained from primary data and secondary data. Data collection techniques use interviews, and observations, while the data analysis techniques used are data reduction and data presentation. For checking the validity of the data used triangulation techniques. The results showed that the process of internalizing multicultural values in religious institutions of Islamic boarding schools in Semarang Regency uses multicultural knowing and multicultural feeling. The implementation of multicultural values has a positive impact on the attitude of students in Semarang district, this positive attitude is implemented in the interaction of daily activities such as equality, justice, tolerance, respect, responsibility, and accepting differences.